The Analysis Effect Prenatal Yoga and the Expression gen MRHR-CRHR1 and mRNA FKBP5 with Real Time-PCR - Ruqaiyah1,2, Nusratuddin Abdullah3 , Mochammad Hatta4 , Syarfianty Arifuddin5 , Saidah Syamsuddin5 , (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Stress triggers the release of corticotrophic release factor (CRF) from the hypothalamus whichin turn stimulates the anterior pituitary to release adrenocorticotrophic hormone (ACTH).Methods: The design of this study is a quasi-experimental approach / quasi experimental and one groupdesign pre and post test design with group control. The sample in this study amounted to 24 respondentsResults: Based on the results of the study showed that the sample LA24 (7,935) was the highest sample foldfold change and the lowest in the sample LA15 (6,194). Whereas in the post test results it was found thatthe LB18 sample (10,580) was the highest sample in fold change and the lowest was in the LB15 sample(8,472).Conclusion: There is a significant relationship / correlation between CRHR1 levels and FKBP5 levels (p =0.001 <?). This is indicated by the high / strong correlation coefficient value which is 0.846. A positive valueat 0.846 indicates that there is a positive relationship or a concomitant relationship, namely the influence ofyoga exercises will result in a decrease in CRHR1 levels and will further reduce the effect of FKBP5 levelsin third trimester pregnant women.